2020
DOI: 10.1093/annweh/wxaa044
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak in Italy: Protecting Worker Health and the Response of the Italian Industrial Hygienists Association

Abstract: Abstract The number of people infected with severe acute respiratory syndrome—coronavirus 2 (SARS-CoV-2), i.e. the virus causing coronavirus disease (COVID-19), is dramatically increasing worldwide to the size of a pandemic. At the time of writing Italy is ranking first among countries both in terms of number of COVID-19 confirmed cases and in terms of number of deaths. Such a wide spread of COVID-19 has led to concern among workers who are facing the risk of bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 10 publications
7
60
0
9
Order By: Relevance
“…In this study, we found that Wuhan residents were more worried than non-Wuhan residents were. Cities in Italy, whose epidemic was once the most severe among the cities in Europe, had similar cases [24]. A third of people experienced symptoms of mild/moderate and severe distress, which were associated with worries about dying in cases of contagion [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Wuhan residents were more worried than non-Wuhan residents were. Cities in Italy, whose epidemic was once the most severe among the cities in Europe, had similar cases [24]. A third of people experienced symptoms of mild/moderate and severe distress, which were associated with worries about dying in cases of contagion [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nesse caso, o estudo indica que os profissionais sejam orientados adequadamente sobre diagnóstico e manejo de pacientes com a doença e as adaptações necessárias em sua prática profissional 15 . Spinazzè et al 9 destacaram a necessidade de conhecimento profissional no campo da Higiene Ocupacional para enfrentar o contexto de emergência, que exige a tomada de decisões baseadas em evidências fornecidas pela literatura científica disponível, por organismos nacionais e internacionais e pela observância das disposições legais. Nesse sentido, destaca a importância da circulação de orientações operacionais para todas as categorias envolvidas no serviço de saúde, com o objetivo de traduzir indicações gerais em procedimentos operacionais claros, a serem adotados nos locais de trabalho.…”
Section: Conhecimentos Sobre a Covid-19 E Atitudes De Profissionais Dunclassified
“…Diversos estudos nacionais e internacionais têm sido realizados para investigar a incidência e as repercussões da COVID-19 nos profissionais de saúde, bem como suas formas de transmissão. Organizar e sistematizar este conhecimento é fundamental para fornecer orientações aos gestores e demais tomadores de decisão no sentido de minimizar os riscos, fornecer equipamentos e insumos de proteção e reduzir os casos de afastamento de profissionais por contágio e/ou infecção por COVID-19 9 .…”
Section: Introductionunclassified
“…Work-related preventive checkout medical examinations are carried out at the end of the employment or a relationship similar to employment for health reasons. 13 They are conducted to determine the condition of the target organs according to the specific factor of the work environment to which the employee had been exposed at work. 14 Finally, after the termination of employment or a relationship similar to employment, if the employee so requests, a former employer for whom https://dusevnezdravie.…”
Section: The Essence Of Executing the Employees' Medical Examinatmentioning
confidence: 99%